Educational Leadership in the UAE: A Comparative Analysis of Transformational, Transactional, and Authentic Models - Al Hammoudi, Amnah (2025)
This study examines three prominent leadership theories (transformational, transactional, and authentic theories) to understand how they are applied in the UAE education sector (private and public sectors) and align with national culture, educational policies, and educational/institutional practices. The UAE requires visionary educational leaders who integrate ethical standards with cultural sensitivity to advance national development agendas such as We the UAE 2031 across public and private schooling, as well as higher education. Using a qualitative theoretical approach and comparative document analysis, the study describes transformational leadership as visionary and motivational, transactional leadership as incentive-based and compliance-oriented, and authentic leadership as integrity-driven and self-aware. It evaluates the alignment of these leadership models with Emirati cultural values, educational policies, and institutional practices, drawing on academic literature, government reports, and peer-reviewed research. The conclusions suggest that transformational and authentic leadership approaches most effectively support the UAE’s educational goals for innovation, inclusion, and sustainable improvement, whereas transactional leadership is better suited to ensuring accountability and operational stability than to driving long-term change. The study proposes that educational leaders in the UAE should adopt blended, transformative and authentic leadership practices grounded in ethical clarity, transparency, and cultural understanding to guide school and university development and shape future-ready learning environments.